Analysis of Risk Factors for Low Back Pain in Mothers Pregnant in the Third Trimester at Anugerah Clinic Deli Serdang - Homitta Juliana br Simatupang; Johanna Fransiska Wijaya; Dewi Sartika (Journal of Social Research, 2025)
Back pain is a common complaint experienced by pregnant women, particularly in the later stages of pregnancy. It usually occurs in the lumbosacral area due to increased gestational age, parity, and physical activity that place pressure on the spine and surrounding muscles. This study aims to analyze the risk factors for back pain in pregnant women during the third trimester. This research is an analytical study with a cross-sectional design. The study was conducted at Anugerah Clinic Deli Serdang. The study population consisted of 52 participants, with a sample size of 35 respondents selected purposively. Data analysis was performed using univariate and bivariate methods with the Chi-Square test at a 95% confidence level (? = 0.05). The results showed that age, occupation, parity, and physical activity had a significant effect on back pain among pregnant women in the third trimester at Anugerah Clinic Deli Serdang, with each p-value demonstrating statistical significance (p = 0.005; p = 0.012; p = 0.001; and p = 0.039), all below the 0.05 threshold. Further researchers are encouraged to examine additional factors that may influence back pain in third-trimester pregnant women, such as stress, posture, and lifestyle. A qualitative or mixed-methods approach could be employed to explore more deeply the experiences of both healthcare providers and patients.